To a critique of space in architectural discourse - Петр Капустин (Проект Байкал)
What is it worth to constantly use the word ‘space’ in contexts related to architecture, urbanism or even ‘new urbanism’? Is there anything real and effective behind it so that we can work with or at least adequately understand and reliably use it in professional and common cultural communications? Where did the habit of using this word come from and what has it replaced? The roots of these questions are in new European rational thinking, but today we are reaping the fruits. In the article, the structure of which imitates I. Kant’s Critiques, the author makes an attempt to critically comprehend these questions.